2005
DOI: 10.2146/ajhp040549
|View full text |Cite
|
Sign up to set email alerts
|

Certified pharmacy technicians’ views on their medication preparation errors and educational needs

Abstract: A nationwide sample of certified pharmacy technicians ranked interruptions and inadequate staffing as the factors contributing most to their medication preparation errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Lastly, reducing medication errors will require increased emphasis on education about drug-related iatrogenic disease 35. The teaching and training of health professionals is recognized as an important tool to prevent mistakes and increase patient safety 36…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, reducing medication errors will require increased emphasis on education about drug-related iatrogenic disease 35. The teaching and training of health professionals is recognized as an important tool to prevent mistakes and increase patient safety 36…”
Section: Discussionmentioning
confidence: 99%
“…A prerequisite for such organization of work is a defined policy for emergency issuing of goods, which is necessary due to the nature of work in a hospital. Our assessment, based on the experience and findings of the authors of papers [10][11][12][13][14][15] who researched the effect of multitasking and interruptions on the pharmacy employees and processes, is that such improvements will lead to a decrease in the number of errors in the pharmacy processes. This will result in greater patient satisfaction and a better balance in the employees' work.…”
Section: Resultsmentioning
confidence: 99%
“…Interruptions and distractions at work are recognized by pharmaceutical technicians as factors that have the biggest impact on the medication preparation errors in a pharmacy [10]. These factors also prolong the time required for standard activities done by pharmacists and pharmaceutical technicians by 27% on average [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, continuing education is not required among all pharmacy technicians, and on the job training may be inconsistent and depend on the availability and ambition of the pharmacy technician. In a recent study, only 16.8% of pharmacy technician respondents reported that, in their most recent medication preparation error, pharmacists provided instruction on how to reduce the chance of a similar error in the future [ 42 ]. Findings from our study indicate that pharmacist-technician working relationships can be improved by pharmacists trusting, empowering, reassuring and providing positive reinforcement to help a pharmacy technician to gain confidence and knowledge in his or her roles.…”
Section: Discussionmentioning
confidence: 99%